Biochemistry ([S.l.] : Mona Group [production company] ; [S.l.] : Biodisc [distributor], 1998)
Contains basic chemistry, enzymology, bioenergetics, metabolism, macromolecular assebly & modification, the flow of genetic information, signal transduction, molecular biology techniques
System requirements: 486 processor (Pentium or better), running Microsoft Windows 3.1 or Windows 95 or NT, 16MB of RAM or better, 4X or better CD-ROM drive, Super VGA monitor, sound card
Keywords: Biochemistry; Biology